(3JChjd GdTQjYI hMbGFbgGs - (3GdbGVj GdfYeGf Hf Mjhf , CHh Mfjag GdfYeGf Hf eMeO Hf efUhQ Hf CMeO Hf Mjhf GdeUQj,J (B363 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi de JSHb YdI ajchf ehdhO Ghde JMW Hg faS hdG Ybd ajchf ehLhO Chde jhLO s
(3BNQgG (B:s
(3hSFd ehdGfG GdGeGe GdeYR dOjf Gddg CejQ GdeDefjf Yf LdhS GdfHi ai GdeSLO Edi Cf JWdY GdTeS s
(3Ufag GdeYR dOjf Gddg GdaGWeis
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B106s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs